ANALISIS KUALITAS PELAYANAN PADA TRANSPORTASI PUBLIK “SI BENTENG” DI KOTA TANGERANG: (Studi Kasus: Trayek AP 1-03 Situ Bulakan Periuk - Gerbang Taman Cibodas) - Marthalina, Grecia Lusiana; Oktariyanda, Trenda Aktiva (Publika, 2024)
Public transportation will connect people to various public sectors, therefore the implementation of public transportation plays an important role in encouraging community mobility, especially in urban areas. A city in Indonesia that regulates its own transportation is Tangerang City. By launching Angkot Si Benteng, the Tangerang City government became the only local government in Banten Province that regulates its own public transportation. Tangerang City Mayor's Regulation (PERWALI) No. 26/2020 stipulates that this regulation is managed by PT Tangerang Nusantara Global as the BUMD of Tangerang City. In its implementation, there are several problems, such as the long time to wait for angkot to arrive, Si Benteng angkot not operating during operational hours, and passengers being picked up and dropped out of place. This research analysis is based on the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 29 of 2015 concerning Minimum Service Standards for Transportation of Persons by Public Motorized Vehicles on Tracks consisting of security, safety, comfort, affordability, equality and regularity. This research uses quantitative methods and descriptive approaches, with data collection techniques through questionnaires, observations, literature reviews and interviews. The results of this study showed that the overall quality of service of Angkot Si Benteng AP 1-03 in Tangerang City can be categorized as very good with a total percentage of 83.96%, while the percentage value on each indicator is security of 89.6%, safety of 84.6%, comfort of 84.2%, affordability of 94.4%, and regularity of 73.12%.